Hypoxia responsive nano-drug delivery system based on angelica polysaccharide for liver cancer therapy - Xue Liu; Zhenfeng Wu; Chunjing Guo; Huimin Guo; Yanguo Su; Qiang Chen; Changgang Sun; Qingming Liu; Daquan Chen; Hongjie Mu (Taylor & Francis Group, 2022)
Based on the tumor hypoxic microenvironment and the new programmed cell death mode of combined ferroptosis, an angelica polysaccharide-based nanocarrier material was synthesized. The polymer contains hydrophilic angelica polysaccharide (ASP) that is linked by azobenzene (AZO) linker with ferrocene (Fc), and then the side chain was covalently modified with arachidonic acid (AA). It was postulated that the polymer micelles could work as an instinctive liver targeting drug delivery carrier, owing to the existence of ASP with liver targeting. Moreover, the aim was to engineer hypoxia-responsive polymer micelles which was modified by AA, for selective enhancement of ferroptosis in solid tumor, via diminishing glutathione (GSH) under hypoxia. Finally, we synthesized the amphiphilic polymer micelles AA/ASP-AZO-Fc (AAAF) by self-assembling. The structure of AAAF was confirmed by 1H-NMR and FT-IR. Then, we exemplified the hydrophobic medication curcumin into polymer micelles AAAF@Cur, which has smooth and regular spheres. In vitro release test affirmed that AAAF@Cur can achieve hypoxia response to drug release. In addition, a series of cell experiments confirmed that hypoxia could enhance cell uptake and effectively improve the proliferation inhibitory activity of HepG2 cells. In conclusion, AAAF, as an effective cell carrier, is expected to develop in sensitizing ferroptosis and anti-tumor.